Exosomes and their cargo are important regulators of cell function in endometriosis. Issue 3 (September 2021) - Freger, Shay; Leonardi, Mathew; Foster, Warren (George)
Abstract: Endometriosis is a chronic oestrogen-dependent gynaecological disorder characterized by non-menstrual pelvic pain, infertility and the extrauterine growth of endometrial-like glands and stroma. It has been noted that the eutopic endometrium of women with endometriosis is functionally distinct from that of women without endometriosis. Moreover, ectopic endometrial implants are functionally different from the eutopic endometrium of women with endometriosis. However, the mechanisms directing these differences are ill-defined. It is proposed here that small membrane-bound extracellular vesicles called exosomes are important vehicles in the protection and transport of signalling molecules central to the dysregulation of endometrial function in women with endometriosis. Therefore, a critical review of the literature linking exosomes and their cargo to the pathobiology of endometriosis was conducted. Circulating peritoneal fluid and endometrial cell exosomes contained long non-coding RNA, miRNA and proteins involved in histone modification, angiogenesis and immune modulation that differed significantly in women with endometriosis compared with controls. Moreover, experimental evidence supports a role for exosomes and their cargo in angiogenesis, neurogenesis, immune modulation and endometrial stromal cell invasion. It is therefore suggested that exosomes play an important role in the pathophysiology of endometriosis.